Pengembangan MEPTISAN untuk Meningkatkan Hasil Belajar Siswa Kelas 5 SD - Indra Kartika Sari; Mawardi Mawardi (STKIP Singkawang, 2020)
21st Century learning ideally utilizes rapidly developing technology. The writing of this article aims to develop Android-based thematic learning media to improve learning outcomes for 5th grade students. The type of research used is Research and Development (R&D). From the results of the preliminary study the learning media used by the teacher are only in the form of pictures and visual aids which each student cannot try on their own because, the limited number of learning media. Based on the results of a preliminary study the author intends to develop MEPTISAN products to improve student learning outcomes for 5th grade students. The product draft was tested by material experts, learning design experts and learning media experts. The results of the material expert validation obtained a score of 90.9%. The results of the learning design expert validation obtained a score of 90%. The results of the learning media expert validation obtained a score of 83.1%. The score is in the category very high and MEPTISAN products are suitable to use for learning.